Correlations of Lewis acidic sites of nickel catalysts with the properties of the coke formed in steam reforming of acetic acid. (April 2022) - Wang, Yiran; Zhang, Zhanming; Zhang, Shu; Wang, Yi; Hu, Song; Xiang, Jun; Wei, Tao; Niu, Shengli; Hu, Xun
Abstract: Coking is a major challenge in the reactions of steam reforming. In addition to the nature of metal species, the properties of carrier also affect coking behaviors of a reforming catalyst. In this work, we prepared nickel carried on Al2 O3, SiO2 or the molecular sieves (25-H, 38-H) for assessed in steam reforming of acetic acid. The Ni/Al2 O3 catalyst contained abundant Lewis acidic sites while the Ni/SiO2, Ni/38-H and Ni/25-H catalysts did not. The Lewis acidic sites in Ni/Al2 O3 induced the polymerisation reactions to form the polymeric coke, which wrapped metallic nickel species and was the primary reason for deactivation of catalyst, even though the amount of coke was small. The substantial amount of coke formed over the other three catalysts did not lead to rapid catalyst deactivation. With the form of carbon nanotube or other forms was mainly the type of catalytic coke, depending on characteristic of the carrier. Comparing with the polymeric coke in the catalyst of Ni/Al2 O3, the catalytic coke had a high C/H ratio, a much higher thermal stability and was more aromatic rich. Graphical abstract: Image 1 Highlights: Ni/Al2 O3 has abundant Lewis acidic sites while Ni/SiO2, Ni/38-H and Ni/25-H do not. The Lewis acidic sites induced polymerisation reactions to form polymeric coke. Small amount of polymeric coke deactivates catalyst, while catalytic coke does not. Catalytic coke in Ni/SiO2, Ni/38-H and Ni/25-H are in carbon nanotube or other form. Catalytic coke has a high C/H ratio, high thermal stability and more aromatic rich.